Pengaruh Persediaan terhadap Profitabilitas PT Dok & Perkapalan Bahari: - Yuli Supodo (LPPM Institut Nasional Laa Roiba Bogor, 2020)
ABSTRACT Industrial or trading companies always keep supplies of raw materials and other supporting materials. Without an inventory, the entrepreneur will be faced with the risk that the company at one time cannot meet the needs of consumers and it also means that the company will lose the opportunity to earn the profit it should get. This study aims to discuss and analyze the Influence of Inventory on the Profitability of PT Dok & Perkapalan Bahari (Persero). The research method is an explanatory survey method, using a quantitative method with primary data. With the research results. The effect of inventory on positive profitability with the results using the method of cost of goods an average of 7,107,143, -. Keywords: inventory, production, profitability